THE IMPORTANCE OF FUNDAMENTAL ASPECTS FOR INVESTORS: PURCHASE OF STOCK MANUFACTURING COMPANIES - Fandi - Kharisma (AKUNTABILITAS, 2019)
Investors need to consider to make an investment decision, which is to use the information from the financial statements. The financial statements made by the company provide a lot of information including assets, debts, capital and corporate profits. Information about company profits is most often used by investors in making investment decisions. An investor should not only look at the net income statement obtained in the financial statements of public companies, but also must conduct an analysis all of the issuer's financial statements. Capital market is one of the business alternatives that can provide benefits. So that all information can be used as input to assess stock prices. The analytical tool used in this study is to use a regression based on the classical assumption test so that the results of the study are valid . This study found that fundamental aspects such as net income, dividends and earnings per share had a significant positive effect on increasing stock prices of manufacturing companies.